2012
DOI: 10.1242/dmm.007872
|View full text |Cite
|
Sign up to set email alerts
|

ROS constitute a convergence nexus in the development of IGF1 resistance and impaired wound healing in a rat model of type 2 diabetes

Abstract: SUMMARYAn indolent non-healing wound and insulin and/or insulin-like growth factor (IGF1) resistance are cardinal features of diabetes, inflammation and hypercortisolemia. Little is known about why these phenomena occur in so many contexts. Do the various triggers that induce insulin and/or IGF1 resistance and retard wound healing act through a common mechanism? Cultured dermal fibroblasts from rats and full-thickness excisional wounds were used as models to test the premise that reactive oxygen species (ROS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 62 publications
3
29
0
Order By: Relevance
“…Majmundar et al [7] found a loss of sensitivity of the IGF-1 receptor at 0.5% O 2 in C2C12 cells. Such a loss of sensitivity has been correlated with an accumulation of ROS in cultured fibroblasts from diabetic rats [17]. In our study, cultured L6 myoblasts at both 21% and 1% O 2 exhibit a higher TBAR accumulation compared to 5% O 2 .…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…Majmundar et al [7] found a loss of sensitivity of the IGF-1 receptor at 0.5% O 2 in C2C12 cells. Such a loss of sensitivity has been correlated with an accumulation of ROS in cultured fibroblasts from diabetic rats [17]. In our study, cultured L6 myoblasts at both 21% and 1% O 2 exhibit a higher TBAR accumulation compared to 5% O 2 .…”
Section: Discussionsupporting
confidence: 67%
“…In L6 myoblasts 5% O 2 seems to be the optimal condition for the best balance between the TBARS production and detoxification. At 1% O 2 we can suggest that the oxidative stress is very high and the low activity of GPx does not allow the removing of ROS, which bind to cellular molecules such as IRS and alter the differentiation [17]. At 21% O 2 the high production of TBARS is detoxified by glutathione peroxidase, which allows the differentiation to occur.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Immune response alterations and carcinogenesis ILP molecules have been reported to play a crucial role in altered inflammatory responses to infectious challenge commonly observed in insulin resistance-related metabolic disorders (Fenton et al 2009, Bitar & Al-Mulla 2012.…”
Section: Insulin Resistance Immune Response Alterations and Cancer:mentioning
confidence: 99%